Estrategias didácticas para fortalecer fluidez y comprensión lectora en la educación rural - Torres Pérez, Germán Edgardo; Dávila Sanabria, Doris Teresa (Universidad Pedagógica y Tecnológica de Colombia, 2019)
This research reflects on the fluency as a skill for reading comprehension from the Escuela Nueva model, as a general objective to describe the incidence of fluency in reading comprehension in elementary school students at La Chorrera Headquarters of the Technical Educational Institution. Industrial and Minera Paz De Rio in the department of Boyacá, this institution is of rural character. It was framed within a qualitative approach, since reading is a topic of relevance and significance for the acquisition of knowledge where fluency is analyzed as an ability for reading comprehension and this is characterized from a quantitative instrument standardized test from a perspective qualitative to recognize the impact on the strengthening of reading comprehension. The type of research is Action, because tasks are implemented for the development of oral expression skills, specifically on fluency. The question that guides the investigation is: How does the fluency in reading comprehension influence from the Escuela Nueva model?